Mortality of individuals in a long-term cohort exposed to polybrominated biphenyls (PBBs) - Metrecia L. Terrell; Amila Adili; Robert B. Hood; Matthew P. Bursley; Hillary Barton; Melanie Pearson; Michele Marcus (Environmental Health)
Abstract Background This study is a long-term follow-up of individuals exposed to polybrominated biphenyls (PBBs). Widespread contamination of PBBs began in 1973 in Michigan when PBBs entered the food chain. PBBs are synthetic chemicals that were once used in industrial products. Their production in the United States ended following this incident. PBBs and other brominated flame retardants belong to a class of persistent organic pollutants that have been shown to affect human health. We conducted this study to investigate whether PBB exposure was associated with all-cause or cause-specific mortality risk. Methods We included cohort data from 1976 (when the study began) and linked to National Death Index data obtained through the early release of 2021. Serum PBB concentrations were measured at enrollment in the study. We used survival analysis to estimate sex-specific hazard ratios (HR) and 95% confidence intervals (CI), adjusting for age and other important risk factors. The mortality study included 3,954 individuals. Results In age-stratified analyses, higher PBB exposure was not associated with all-cause mortality risk in males or females. In cause-specific analyses conducted in the 16 or older group, we found no association between PBB exposure and circulatory system disease mortality. For all-cancer mortality, we found higher PBB exposure associated with increased risk of mortality in females (HR: 1.50, 95% CI: 1.02–2.22), which was inversed in males (HR: 0.68, 95% CI: 0.46–1.01). BMI appeared to modify the association between PBB exposure and all-cause mortality risk in males and all-cancer mortality risk in males and females. Conclusions This comprehensive study found that the association between PBB exposure and cancer mortality risk varied by sex. Further research is needed to understand these sex-specific differences.